Analisis Penerapan Akuntansi Aset Tetap pada Koperasi di Kota Gorontalo - Aristo Kurniawan Hulopi; Hartati Tuli; Usman (Jambura Accounting Review, 2021)
The research aims to know the implementation of Financial Accounting Standards for Entities without Public Accontability (SAK-ETAP) Chapter 15 on Fixed Assets in Cooperatives in Gorontalo City. The research applies descriptive quantitavie method. There are 10 coorperatives in Gorontalo City as the sample which are taken by using purposive sampling technique. The data collection technique uses questionnaires while the validity and reliability test uses the SPSS program. The finding indicates that the 10 cooperatives classified as healthy by the Department of Manpower, Cooperatives, and SMEs of Gorontalo City have not fully implemented the SAK-ETAP Chapter 15 on Fixed Assets. There are only 6 out of the 16 statements which are fully implemented according to the indicators of SAK-ETAP Chapter 15 on Fixed Assets, and 10 statements are not fully implemented according to the applicable standards. This is due to the cooperatives’ lack of understanding of humman resources regarding SAK-ETAP Chapter 15 on Fixed Assets.